Design and fabrication of a lumbar interbody fusion spine cage combining titanium and PEEK materials - Yudan Whulanza (BKS-TM Indonesia, 2025)
Lower back pain (LBP) is a common condition that significantly affects patient quality of life. One of the pathological causes of LBP is degenerative disk disease (DDD), resulting from the degeneration of the intervertebral disc (IVD). A surgical option for addressing this is transforaminal lumbar interbody fusion (TLIF), which involves the use of an implant known as a spine cage to maintain spacing between vertebrae during bone fusion. Spine cages are commonly made from either polyether ether ketone (PEEK) or titanium, both of which have distinct advantages and limitations. PEEK exhibits a bone-like elastic modulus but limited osseoconductivity, whereas titanium offers good osseoconductivity but an elastic modulus much higher than bone. This study proposes a hybrid spine cage combining both materials: PEEK machined via computer numerical control (CNC) machining and titanium fabricated using selective laser melting (SLM). The cage features a banana shape, nose insertion, pins-and-holes connection system, and dimensions customized for the Indonesian lumbar morphometry. Realized prototype showed a maximum margin of 3.9% for titanium part and 2.14% for PEEK part. Further results showed a compressive elastic modulus of 1.36 GPa, indicating the current model followed mechanical property of titanium material.